Physicochemical properties and photodynamic therapy activities of indium and zinc phthalocyanine-nanoparticle conjugates - Dube, Edith (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
The syntheses and characterization of symmetric and asymmetric Pcs functionalized at the peripheral position are reported. The Pcs contain either zinc or indium as central metals and have carboxyphenoxy, phenoxy propanoic acid, benzothiazole phenoxy, thiophine ethoxy or di-O-isopropylidene-Î±-D-glucopyranose as ring substituents. The Pcs were linked to NPs via an amide bond or through self-assembly. The photophysics and photochemistry of the Pcs were assessed when alone and with conjugates. All the studied Pcs showed good photophysicochemical behaviour with relatively high triplet and singlet oxygen quantum yields corresponding to their low fluorescence quantum yield. The Pcs with indium in their central cavity exhibited higher triplet and singlet oxygen quantum yields in comparison to their zinc counterparts due to the heavy"“atom effect obtained from the former. Asymmetrical Pcs displayed higher triplet and singlet oxygen quantum yields than their symmetrical counterparts. The triplet quantum yield, generally increased on linkage to nanoparticles (NPs) due to the heavy"“atom effect of gold and silver in NPs. The conjugates to gold nanospheres yielded higher triplet and singlet quantum yields than their gold nanotriangles counterparts due to the higher loading by the former probably encouraged by their relatively small particle size. The in vitro dark cytotoxicity and photodynamic therapy of selected Pc complexes and conjugates against MCF-7 cells was tested. All studied Pc complexes and conjugates showed minimum dark toxicity making them applicable for PDT. All complexes displayed poor phototoxicity with >50ÃŽll viability at concentrationsâ‰¤ 160Î¼g/mL, however the conjugates showed<50% cell viabilityatconcentrationsâ‰¤ 160Î¼g/mLprobably due to the enhanced singlet oxygen quantum yield. The findings from this work show the importance of linking photosensitises such as phthalocyanines to metal nanoparticles for the enhancement ofsinglet oxygen quantum yield and ultimately the photodynamic effect.
Keywords: Indium; Zinc; Phthalocyanines; Breast -- Cancer -- Photochemotherapy; Nanoparticles